Determining The Need of Tank Cars In The Fuel Distribution Process to Pertashop at XYZ Company - Yunanik; Muhammad Siddiq Abdillah (Jurnal Rekayasa Sistem & Industri, 2023)
XYZ Lahat Company is one of the companies operating in South Sumatra region. This company uses Fleetor Tank Car (TC) as a mode of transportation in distributing fuel products to Pertashop. The constructionof Pertashop in Lahat, South Sumatra, has increased 22% since beginning of the program in May 2021.There are partners who join the construction of 5 units/month of Pertashop and the growth rate ofPertashops affects the number of Thruput by 143 KL/month, whereas the needs for transportation is alsoincreasing, such as the number of needs for fuel products. The method used for mapping is clustering andfor calculation used proportional. The data analysis includes the capability of the car fleet. In conclusion,321 Fleets can be fulfilled with an increase in ritase of 6.02 rit/day which can optimize the fuel distributionprocess and meet consumer needs.